THE EFFECTS OF VOCABULARY MASTERY AND STUDENT’S PERCEPTION ON TEACHING MATERIAL TOWARDS WRITING SKILL - Agus Wilson (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2015)
This research is aimed as follows : To get emperical data and analyze the effects of vocabulary mastery and student’s perception on teaching material towards writing skill at State Senior High Schools in South Tangerang. The research was held at SMAN 5 and SMAN 6 in South Tangerang, the population of 400 students with a sample that is taken randomly about 40 students. Data collective done by giving test for writing skill (make a composition or an essay about their life), test for vocabulary mastery (multiplechoice/ 20 items), and test for student’s perception on teaching material (questioner/20 items) given to class at SMAN 5 and SMAN 6. The result of study identifies there are effectsbetween Vocabulary Mastery and Student’s Perception on Teaching Material towards Student’s Writing Skill.Keywords: Vocabulary Mastery, Students’ perception on Teaching Material, and Writing Skill.